Multi-Residue Determination of 244 Chemical Contaminants in Chicken Eggs by Liquid Chromatography-Tandem Mass Spectrometry after Effective Lipid Clean-Up - Lin Zhang; Qi Jia; Guangqin Liao; Yongzhong Qian; Jing Qiu (Agriculture, 2022)
In this study, we aimed to establish a multi-residue analytical method for the simultaneous detection of chemical contaminants in eggs. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), we developed an analytical method that can separate 244 compounds (including β-agonists (25), imidazole and benzimidazoles (31), sulfonamides (22), antihistamines (10), β-lactam (5), insecticides (7), quinolones (24), non-steroidal anti-inflammatory drugs (13), and steroidal hormones (38)) within 30 min. A new enhanced matrix removal-lipid (EMR-Lipid) material was used as a purified sorbent in the QuEChERS clean-up method. Excellent linearity (r > 0.9905) was achieved. Additionally, recoveries ranged between 51.33% and 118.28%, with repeatability (RSDr) and reproducibility (RSDwR) in the range of 1.01–14.22% and 1.08–14.96%, respectively. In all of the compounds, low limits of quantification (LOQs) ≤ 5 μg kg−1 were found. Meanwhile, the detection limit (CCα) and detection capability (CCβ) were 1.88–40.60 μg kg−1 and 2.85–407.19 μg kg−1, respectively. In conclusion, the evaluated method was shown to provide reliable screening, quantification, and identification of 244 multi-class chemicals in eggs and was successfully applied in real samples.